Job satisfaction, perceived performance and work regime: What is the relationship between these variables? - Angelie Pinheiro; Ana Palma-Moreira (Administrative Sciences, 2025)
The objectives of this study were to study the effect of job satisfaction on performance and whether this relationship is moderated by work regime (face-to-face, hybrid and remote) and to study the effect of work regime on performance and whether this relationship is mediated by job satisfaction. The sample consisted of 332 participants working in organizations based in Portugal. The results show that job satisfaction positively and significantly correlates with perceived performance. The work regime significantly affects perceived performance, with hybrid workers having the highest perceived performance. The work regime significantly affects job satisfaction, with remote workers having the highest levels of job satisfaction. Job satisfaction has a mediating effect on the relationship between work regime and perceived performance. Contrary to expectations, the work regime does not moderate the relationship between job satisfaction and perceived performance. Human resource management is recommended to keep employees satisfied and boost their performance. This study has shown how hybrid and remote working arrangements are fundamental to this.
Keywords: 350; job satisfaction; perceived performance; work regime; organizational behavior; well-being; quantitative study